Stem Cell Based Approaches to Modulate the Matrix Milieu in Vascular Disorders - S, Sajeesh; Dahal, Shataakshi; Bastola, Suraj; Dayal, Simran; Yau, Jimmy; Ramamurthi, Anand (Frontiers in Cardiovascular Medicine, 2022)
The extracellular matrix (ECM) represents a complex and dynamic framework for cells, characterized by tissue-specific biophysical, mechanical, and biochemical properties. ECM components in vascular tissues provide structural support to vascular cells and modulate their function through interaction with specific cell-surface receptors. ECM–cell interactions, together with neurotransmitters, cytokines, hormones and mechanical forces imposed by blood flow, modulate the structural organization of the vascular wall. Changes in the ECM microenvironment, as in post-injury degradation or remodeling, lead to both altered tissue function and exacerbation of vascular pathologies. Regeneration and repair of the ECM are thus critical toward reinstating vascular homeostasis. The self-renewal and transdifferentiating potential of stem cells (SCs) into other cell lineages represents a potentially useful approach in regenerative medicine, and SC-based approaches hold great promise in the development of novel therapeutics toward ECM repair. Certain adult SCs, including mesenchymal stem cells (MSCs), possess a broader plasticity and differentiation potential, and thus represent a viable option for SC-based therapeutics. However, there are significant challenges to SC therapies including, but not limited to cell processing and scaleup, quality control, phenotypic integrity in a disease milieu in vivo, and inefficient delivery to the site of tissue injury. SC-derived or -inspired strategies as a putative surrogate for conventional cell therapy are thus gaining momentum. In this article, we review current knowledge on the patho-mechanistic roles of ECM components in common vascular disorders and the prospects of developing adult SC based/inspired therapies to modulate the vascular tissue environment and reinstate vessel homeostasis in these disorders.